Biliary reconstructive techniques and associated anatomic variants in adult living donor liver transplantations: The adult‐to‐adult living donor liver transplantation cohort study experience. Issue 12 (20th November 2017) - Baker, Talia B.; Zimmerman, Michael A.; Goodrich, Nathan P.; Samstein, Benjamin; Pomfret, Elizabeth A.; Pomposelli, James J.; Gillespie, Brenda W.; Berg, Carl L.; Emond, Jean C.; Merion, Robert M.
Abstract : Living donor liver transplantation (LDLT) is a technically demanding endeavor, requiring command of the complex anatomy of partial liver grafts. We examined the influence of anatomic variation and reconstruction techniques on surgical outcomes and graft survival in the 9‐center Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study (A2ALL). Data from 272 adult LDLT recipients (2011‐2015) included details on anatomic characteristics and types of intraoperative biliary reconstruction. Associations were tested between reconstruction technique and complications, which included first biliary complication (BC; leak, stricture, or biloma) and first vascular complication (VC; hepatic artery thrombosis [HAT] or portal vein thrombosis [PVT]). Time to patient death, graft failure, and complications were estimated using Kaplan‐Meier curves and tested with log‐rank tests. Median posttransplant follow‐up was 1.2 years. Associations were found between the type of biliary reconstruction and the incidence of VC ( P = 0.03) and BC ( P = 0.05). Recipients with Roux‐en‐Y hepaticojejunostomy had the highest probability of VC. Recipients with biliary reconstruction involving the use of high biliary radicals on the recipient duct had the highest likelihood of developing BC (56% by 1 year) compared with duct‐to‐duct (42% by 1 year). In conclusion, the varied surgical approaches in the A2ALL centers offer a novel opportunity to compare disparate LDLT approaches. The choice to use higher biliary radicals on the recipient duct for reconstruction was associated with more BC, possibly secondary to devascularization and ischemia. The use of Roux‐en‐Y biliary reconstruction was associated with VCs (HAT and PVT). These results can be used to guide biliary reconstruction decisions in the setting of anatomic variants and inform further improvements in LDLT reconstructions. Ultimately, this information may contribute to a lower incidence of technical complications after LDLT. Liver Transplantation 23 1519–1530 2017 AASLD.